The Internal Organization of the Firm and Price Formation: An Illustrative Case - Alt, Richard M. (Quarterly Journal of Economics, 1949)
I. Introduction, 92. — II. Large size of the store unit, 94. — III. Administrative organization, 96. — IV. Budgetary procedures, 98. — V. Inter-unit controls, 103. — VI. Owner-management relationships, 105. — VII. Price policies, 106. — VIII. Conclusion, 110.